The Construction of the Evaluation Index for the Outgoing Auditing of the Natural Resource Assets of Local Leading Cadres Based on the Analytic Hierarchy Process - Jiali Xuan (Applied Bionics and Biomechanics)
As the foundation of human survival and development, natural resources affect every aspect of our lives, including life and health, financial security, and overall social security. This article describes building a system for valuing the assets of good NR in operation for local executives who employ analytic hierarchy process. Based on his bibliographic data, he has a deep understanding of the theoretical issues associated with the process of analytical hierarchy and the uncontrollable control of natural resource assets. In addition, he uses an analytic hierarchy process to create a system of metrics for the external management of local leaders’ NR and analyzes examples through the newly established metrics system. As a result, the current mayor of this case is more than the responsibility of the previous mayor. During the period, natural and environmental conditions improved, especially in the areas of water and air resources, which are more relevant than they are today.